The Contemporary Thai Version of the Kathin Ceremony: Ceremonial Importance of the Distribution of White Envelops and the Money Tree Tradition - Iso, Klairung (Journal of International Buddhist Studies, 2018)
The Kathin ceremony is generally known as a ceremony of the Buddhist laypeople to make an offering of new robes to the monks. The joyfulness of people in the contemporary Thai Kathin festival reflects a fusion of the traditional ritual and the modern socioeconomic context in the Thai society, which can be explained in three points. Firstly, since there is a strong incorporation between Animism, Buddhism and Brahmanism-Hinduism. Kathina reflects a combination of all the three beliefs, conducting good deeds to some sacred things in exchange of the protection from them as in the Animism theme, giving new robes to the monk as the traditional Buddhist scripture allows them to conduct, and putting a great deal of effort to create richness of rituals and processes as the Brahmanism-Hinduism heritage. Secondly, capitalism has trained people heavily on investing for gaining something. Apparently, there are many laypeople who conduct meritorious practices for gaining some instant happiness. Since Kathina is a ceremony recognized to provide a great amount of good result manifestation regarding the Law of Kamma, it is therefore not unusual to find the Thai laypeople who are enjoying enclosing some banknotes into the white envelopes or to attach some banknotes on to the money tree. However, the Law of Kamma is complex. Sometime, it seems a person will spend more than a lifetime to see the results of what one sowed. Being generous or gaining merit acquired by giving, therefore, seems to becomes something to heal people from the everyday traumas of life. In other words, giving is a way to help them emotionally not a way to purify their mind.